Establishment of monoclonal HCC cell lines with organ site-specific tropisms. Issue 1 (December 2015) - Wan, Jinliang; Wen, Duo; Dong, Lili; Tang, Jun; Liu, Dongli; Liu, Yang; Tao, Zhonghua; Gao, Dongmei; Sun, Huichuan; Cao, Ya; Fan, Jia; Wu, Weizhong
Abstract Background Organ site-specific metastasis is an ominous feature for most poor-prognostic hepatocellular carcinoma (HCC) patients. Cancer cell lines and animal models are indispensable for investigating the molecular mechanisms of organ specific tropism. However, till now, little is known about the drivers in HCC metastatic tropism, and also no effective way has been developed to block the process of tropistic metastasis. Methods In this study, we established several monoclonal HCC cell lines from HCCLM3-RFP together with their xenograft models, and then analyzed their metastatic potentials and tropisms using in-vitro and in-vivo assays, and finally elucidated the driving forces of HCC tropistic metastases. Results Six monoclonal cell lines with different organ site-specific tropism were established successfully. SPARC, VCAM1 and ANGPTL4 were found positively correlated with the potentials of lung metastasis, while ITGA1 had a positive relation to lymph node metastasis of enterocoelia. Conclusions By our powerful platforms, HCC metastatic tropisms in clinic could be easily mimicked and recapitulated for exploring the bilateral interactions between tumor and its microenvironment, elucidating the drivers of HCC metastatic tropisms, and testing anti-cancer effects of newly developed agent in pre-clinical stage.